Screening of antifungal compound isolated from catharanthus roseus L. (pink) for biological control of selected plant diseases - Zahari, Rozihawati (2015)
Diseases of rubber (Hevea brasiliensis) caused by pathogens, Rigidoporus microporus, Ganoderma philippii and Phellinus noxius. Fusarium oxysporum,F. solani and Colletotrichum gloeosporioides on chilli (Capsicum annuum) are currently being kept under control with chemical fungicides. However, these fungicides have been shown to have hazardous effects to humans and the ecosystems. To address these problems, the search for an effective and environmentally safe compound to control these harmful pathogens is highly warranted. Thus, in this study, antifungal compounds from selected plants, Aglaia argentea, A. leucophylla, A. grandis, A. odoratissima, A. variisquama,Cassia alata, Catharanthus roseus, Derris elliptica and Tinospora baenzigeri were screened for their effectiveness in controlling the growth of selected fungal pathogens on seedlings. The result showed that C. roseus extract was the most effective in inhibiting the growth of pathogens as the extract contains various antifungal compounds such as phenolics, alkaloids, essential oils and flavonoids. Although the extract of C. roseus contains abundant bioactive compounds, detailed studies on their biological activities on those fungal pathogens have yet to be reported. The C. roseus extracted with dichloromethane (DCM) showed the greatest inhibition zone diameter in controlling R. microporus and F. oxysporum at the values of 11.29 mm and 8.10 mm, respectively, compared to other selected medicinal plant extracts. The C. roseus extract assessed based on conidia and hyphae growth of F. oxysporum and R. microporus, respectively showed minimum inhibition concentration (MIC) and minimum fungicidal concentration (MFC). MIC and MFC results showed that the extract at 270 μg/mL with inhibition value of 0.0 μg/mL was the most effective in controlling the growth of F. oxysporum and R. microporus compared to 200, 140, 70 and 10 μg/mL. The antifungal compound isolated from C. roseus extract was determined through thin layer chromatography (TLC), high performance liquid chromatography (HPLC) and nuclear magnetic resonance (NMR) analysis. Each C. roseus of DCM extracts was marked as CRD5a, CRD5b, CRD5c, CRD5d, CRD5e, CRD5f and CRD5g. The TLC results showed that all of the C. roseus extracts peak with red in colour at Rf= 0.61 at 366 nm wavelength, except for CRD5g. The CRD5d extract was the most effective against G. philippii and R. microporus with inhibition zones of 3.5 and 1.9 mm, respectively, compared to other extracts. However, CRD5g extract was the most effective against F. oxysporum with a value of 3.0 mm compared to other extracts. HPLC results also showed the major peak is at 210 nm. The CRD5d extract isolated contained single compound such as ursolic acid after being detected by NMR analysis. The compound was effective to control R. microporus and G. philippii with inhibition zone values of 4.0 and 3.0 mm, respectively. In addition, the efficacy of C.roseus extracts against F. oxysporum and R. microporus was assessed based on healthy effects percentage of the chilli and rubber seedlings, respectively,by assessing the symptoms on leaves and roots. The assessment was based on disease incident (DI%) and disease suppression (DS%). The DI% results showed that an extract at 2,000 μg/mL was the most effective in controlling F.oxysporum on chilli seedlings with value of 0.0%, compared to 1000 and 1500 μg/mL with values of 60 and 80%, respectively. The DS% results also showed that the extract was most effective at 2000 μg/mL in controlling the growth of R.microporus on rubber seedlings with a value of 100% compared to 1500 and 1000 μg/mL with a value of 0.0%. In conclusion, C. roseus extracted with DCM contains an effective toxin that is detrimental on the plant pathogenic fungi. The C. roseus of DCM extract isolated contains ursolic acid and the compound effective against R. microporus and G. philippii. Hence, C. roseus extract should also be developed as a biofungicide for controlling R. microporus and F.oxysporum on rubber and chilli, respectively.